Immediate effect of stretching and ultrasound on hamstring flexibility and proprioception - Cho, Sung-Hak; Kim, Soo-Han (Journal of Physical Therapy Science, 2016)
[Purpose] This research explored the positive effects of self-myofascial release on hamstring muscular flexibility and proprioception and investigated the effectiveness of the stretch combined with therapeutic ultrasound. [Subjects and Methods] This study included 30 healthy university students with no history of pain in the Achilles tendon or hamstring within the recent 6 months. Each participant completed two experiments. In the first experiment (MS), they completed self-myofascial stretching using a foam roller for 7 days. In the second experiment (MSU), the same participants performed the self-myofascial stretching after the 15-minute application of ultrasound. This study involved a pre- and post-test on hamstring muscle flexibility and hip joint proprioception. [Results] The use of self-myofascial stretching in the MS experiment had a significant effect on hamstring muscle flexibility and hip joint proprioception. However, the addition of ultrasound in the MSU experiment had no additive effect. [Conclusion] Self-myofascial stretching immediately increased hamstring muscle flexibility and improved hip joint proprioception, but the addition of pre-stretch ultra sound provided no further benefit.